SUBSITUSI TEPUNG KACANG HIJAU DALAM PEMBUATAN BOLU PANDAN KUKUS - Surya Aditya Wahyono; Laura Cynthia Grace Lumban Tobing (Akademi Pariwisata NHI Bandung, 2023)
Gluten is a glycoprotein consisting of the components gliadin and glutenin. Gluten is found in many grains such as wheat, rye, oats, barley or wheat flour. Gluten is also often added to food preparations to add texture and volume (Niland and Brooks, 2019). The gluten content contained in wheat flour can cause allergies and intolerance. Gluten causes impaired brain function in people with autism. Many people end up not being able to enjoy processed products that use wheat flour, one of which is sponge cake which is very popular with the public. So we need substitute ingredients that are safe, but still have the taste, texture and aroma that match the original product. In this case, using a substitution of mung bean flour. Mung bean flour contains lots of vitamins, which can be eaten by children, adults, the elderly, and other people who have diseases that cannot consume regular flour. . The benefits of this green bean are that it can facilitate bowel movements and increase enthusiasm for life, can be used as a treatment for hepatitis, sprains, beriberi, puerperal fever, headache or vertigo, restore health, anemia, fluttering heart and dizziness.